2019
DOI: 10.1155/2019/9424605
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Network Analysis Tools in Psychological Networks: Minimal Spanning Trees, Participation Coefficients, and Motif Analysis Applied to a Network of 26 Psychological Attributes

Abstract: The analysis of psychological networks in previous research has been limited to the inspection of centrality measures and the quantification of specific global network features. The main idea of this paper is that a psychological network entails more potentially useful and interesting information that can be reaped by other methods widely used in network science. Specifically, we suggest methods that provide clearer picture about hierarchical arrangement of nodes in the network, address heterogeneity of nodes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 62 publications
(61 reference statements)
1
46
0
Order By: Relevance
“…There are multiple problems in interpreting central symptoms as the most influential, (the most central may be just the end point or just the one with the greatest variability, see: https://psych-networks.com/how-to-not-interpret-centrality-values-in-network-structures/ ) and recently the whole basis of measuring centrality in psychological networks that do not have similar features (serial flow of connections) as social networks, has been challenged [ 20 ]. In the present study, we tried to overcome some of these problems using centrality measures that are not based on shortest path measures (strength centrality) and by taking into account the community structure within the network (participation coefficient) [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple problems in interpreting central symptoms as the most influential, (the most central may be just the end point or just the one with the greatest variability, see: https://psych-networks.com/how-to-not-interpret-centrality-values-in-network-structures/ ) and recently the whole basis of measuring centrality in psychological networks that do not have similar features (serial flow of connections) as social networks, has been challenged [ 20 ]. In the present study, we tried to overcome some of these problems using centrality measures that are not based on shortest path measures (strength centrality) and by taking into account the community structure within the network (participation coefficient) [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, network modelling is currently in its initial stages (Guloksuz, Pries, & van Os, 2017). Although it is shown as a promising tool in obtaining information in a number of research fields, there remain to be limitations and resolution issues (Jones, Heeren, & McNally, 2017;Letina, Blanken, Deserno, & Borsboom, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond these specific results, the current ‘psychonectome’ proof-of-concept approach seems useful to provide further evidence of the mind as a complex network of psychological constructs. The approach of considering topological aspects of the relations between constructs may help to enhance our understanding of psychological functioning as a complex network of interacting elements that are mutually interconnected [1820,137,138]. This unique perspective has become central in fields like neuroscience [25,35] and is likely that can also provide useful insights on the functioning and mechanisms of human mind.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some network theorists have recently suggested that dwelling excessively on the lack of interest of latent variables may misguide the focus from what is more promising in conceptualizing disorders from a NA perspective (i.e., the idea of causally interconnected elements) [16,17]. In this sense, the use of psychological constructs (e.g., traits assessed by questionnaires), and not only elements like symptoms or signs, is beginning to be used in NA (e.g., [1820]) and it could also be possible that, in the future, hybrid models, using not only elements like signs and symptoms but also latent variables, could shed light on the connections between psychological elements [21,22].…”
Section: Introductionmentioning
confidence: 99%